2017
DOI: 10.1159/000481728
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiological Mechanism and Treatment of Secondary Brain Insult of Hypertensive Intracerebral Hemorrhage

Abstract: Hypertensive intracerebral hemorrhage (HICH) is a type of acute cerebrovascular disease with high rates of incidence, mortality, and disability, and is a cause of more frequent instances of secondary brain insult (SBI). In-depth study of the pathogenesis and pathophysiological mechanisms of SBI in HICH contributes to its clinical treatment and prognosis. This article presents a brief summary of the pathophysiological mechanism and treatment of SBI after HICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Pathophysiologically, hyperglycemia is caused by the disruption of blood glucose regulation in the brainstem due to the mass effect of hematoma and brain herniation. 12 Previous studies have shown that the prevalence of hyperglycemia in patients with SICH is 51%. 13 Although a higher cut-off value was used to define hyperglycemia (7.77 mmol/L rather than 6.5 mmol/L), this study showed a higher prevalence of 65%.…”
Section: Discussionmentioning
confidence: 98%
“…Pathophysiologically, hyperglycemia is caused by the disruption of blood glucose regulation in the brainstem due to the mass effect of hematoma and brain herniation. 12 Previous studies have shown that the prevalence of hyperglycemia in patients with SICH is 51%. 13 Although a higher cut-off value was used to define hyperglycemia (7.77 mmol/L rather than 6.5 mmol/L), this study showed a higher prevalence of 65%.…”
Section: Discussionmentioning
confidence: 98%